Lipid metabolism: new twists to the Yin and Yang of PKM2 in cancer. (12th October 2021) - Khateb, Ali; Ronai, Ze'ev A
Abstract : While canonical and non‐canonical functions of pyruvate kinase M2 (PKM2) are recognized to mediate often‐opposing roles in cancer, its contribution to cellular and systemic fatty acid homeostasis remains poorly understood. A new study by Liu et al (2021) uncovers ER transmembrane protein TMEM33 as a novel target of PKM2, which is essential for regulation of cancer cell cholesterol metabolism. These findings highlight the diversity of tissue‐specific functions of PKM2 and potential implications for cancer treatment. Abstract : Recent work reports a novel PKM2‐TMEM33‐SCAP axis for regulation of cancer cell cholesterol metabolism.